Simple, Precise, and Less Biased GMO Quantification by Multiplexed Genetic Element-Specific Digital PCR. (9th October 2021) - Noma, Satoshi; Kikuchi, Yosuke; Satou, Megumi; Tanaka, Tomoki; Takiya, Toshiyuki; Okusu, Hideki; Futo, Satoshi; Takabatake, Reona; Kitta, Kazumi; Mano, Junichi
Abstract: Background: To provide the consumer with choices of genetically modified organisms (GMO) or non-GMO, official food labeling systems were established in many countries. Because the threshold GMO content values were set to distinguish between "non-GMO" and "GMO" designations, GMO content quantification methods are required for ensuring the appropriateness of labeling. Objective: As the number of GMOs is continuously increasing around the world, we set out to develop a low-cost, simple and less biased analytical strategy to cover all necessary detection targets. Methods: Digital PCR methods are advantageous compared to the conventional quantitative real-time PCR methods. We developed a digital PCR-based GMO quantification method to evaluate the GMO content in maize grains. To minimize the analytical workload, we adopted multiplex digital PCR targeting the 35S promoter and the nopaline synthase terminator, which are genetic elements commonly introduced in many GMOs. Results: Our method is significantly simpler and more precise than the conventional real-time PCR-based methods. Additionally, we found that this method enables quantification of the copy number of GMO DNA without double counting multiple elements (35S promoter and nopaline synthase terminator) tandemly placed in a recombinant DNA construct. Conclusion: This is the first report on the development of a genetically modified maize quantification method using a multiplexed genetic element-specific digital PCR method. The tandem effect we report here is quite useful for reducing the bias in the analytical results. Highlights: Multiplexed genetic element-specific digital PCR can simplify weight-based GMO quantification and thus should prove useful in light of the continuous increase in the number of GM events.